444 Partial Transpedicular Thoracic Discectomy With Ultrasonic Aspiration and Ultrasound Guidance for Every Thoracic Disc Herniation: A 43-Patient Case Series and Technical Note Demonstrating Safety and Efficacy. (1st March 2022) - Saway, Brian F.; Alshareef, Mohammed A.; Lajthia, Orgest; Santos, Jaime M.; Cunningham, Coby; Shope, Chelsea; Kalhorn, Stephen P.
Abstract : INTRODUCTION: Thoracic disc herniations (TDHs) are a challenging pathology. A variety of surgical techniques have been used to achieve spinal cord decompression. METHODS: A retrospective review was performed of patients who underwent a thoracic discectomy through the partial transpedicular approach between January 2014 and 2020 by a single surgeon. Variables reviewed included demographics, peri-operative imaging, and functional outcome scores. RESULTS: 43 patients (53% female) underwent 54 discectomies. The most common presenting symptoms were myelopathy (86%), motor weakness (72%), and sensory deficit (65%) with a symptom duration of 9 ± 8.86 months. 23 (42.5%) of discs were fully calcified on imaging and 18 (33.3%) were partially calcified. 33 (61.1%) were giant TDH (>40% canal compromise). Average operative time was 197 ± 77.1 minutes with an average blood loss of 238 ± 250 cc. 6 patients required ICU stays. Hospital length of stay was 4.37± 3.42 days. Of patients with follow-up MRI, 38 of 40 disc-levels (95%) demonstrated <20% residual disc. Post-operative Frankel scores (>3 months) were maintained or improved for all patients with 28 (65.1%) patients having an increase of 1 or greater on their Frankel score. 6 (14%) patients required repeat surgery, 2 of which were due to re-herniation, 2 were from adjacent level herniation and 2 others from wound problems. Patients with calcified TDHs had similar improvement in Frankel grade compared to patients without calcified TDH. Additionally, improvement in intra-operative neuromonitoring was associated with a greater improvement in Frankel grade. CONCLUSION: Here we demonstrate a minimally invasive, posterior approach that utilizes intraoperative ultrasound and ultrasonic aspiration with great outcomes and a complication profile similar or better than other reported case series. This posterior approach is a great complement to the spine surgeon's arsenal for the confident tackling of all TDHs.